Comparative analysis of national essential medicine list for children by Indian academy of pediatrics and pediatric drugs available at a tertiary care teaching hospital in Rajkot, Gujarat, India - Prajapati, Mitalee; Kubavat, Amita; Bhansali, Nishant (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The better medicines for children initiative of the WHO began in December 2007 as a consequence of the World Health Assembly resolution 60.20, when there was evidence that nearly 50% of children under five were dying for preventable diseases for which medicines existed. There is a need to develop “child friendly” formulations and make them available. Methods: This cross sectional study was conducted during September 2015. The availability of essential medicine for children (drugs, strength, and dosage form) was noted down. Drugs which are not listed in the National list of Essential medicines (NLEMc) for children but available in the hospital pharmacy were also noted down. Results: Out of the drugs listed in NLEMc, 86.56% drugs were available in the pharmacy of tertiary care teaching hospital, Rajkot. 57.76% percent of these drug formulations were available as specified in NLEMc and 44.36% of the available drugs had the same strength as specified in NLEMc. For those drugs which are mentioned in NLEMc but not available in the hospital pharmacy, alternative drugs are available for the same indication. Conclusions: Majority of the drugs available in hospital pharmacy of tertiary care teaching hospital, Rajkot are in accordance to NLEMc. However hospital pharmacy is deficient in paediatric formulations and strength in accordance to NLEMc.